Izbastina K., Aipeisova S., Kurmanbayeva M., Kurmantayeva A., Baishanbo A. Review of genus Anthemis L. (Asteraceae) species, stored in some Kazakhstan herbarial funds: Al-Farabi Kazakh national university, Almaty, Kazakhstan 2K. Zhubanov Aktyubinsk regional state University, Aktobe, Kazakhstan 3Institute of botany and phytointroduction, Almaty, Kazakhstan 4Xinjiang medical university, Xinjiang institute of Kazakh drug medicine, Urumqi, China *Е-mail: izbastina.k@gmail.com (Eurasian Journal of Ecology, 2017)
The big and important task is represented by research of rare endangered species for the purpose of their preservation, profound studying of features of rare species of plants and their resources is necessary. The purpose of this work is careful viewing of specific structure of the sort Anthemis L., stored in the herbarial funds of Institute of botany and phytointroduction of Ministry of Education and Science of the Republic of Kazakhstan, Al-Farabi Kazakh National University, K. Zhubanov Aktyubinsk regional state university. For achievement of goals the abstract of types of the sort Anthemis L. is made, meeting in the territory of Kazakhstan by means of critical viewing of the herbarial material which is stored in the herbarial funds. Scientific and practical value are that herbarial samples of the studied type of the sort Anthemis L., met in the territory of Kazakhstan, will be used by students for definition on special courses and on big practical works on botany. As a result of careful viewing, there are 74 herbarial samples of the sort Anthemis L., the abstract of types of the sort Anthemis L. is made in the territory of Kazakhstan, including the location of a type of Anthemis trotzkiana Claus in the research territory (The Aktyubinsk region) is given. According to the results of research, 5 types of the sort Anthemis L. have been noted. They are met in the territory of Kazakhstan (Anthemis trotzkiana Claus, Anthemis candidissima Willd.ex Spreng., Anthemis tinctoria L., Anthemis cotula L., Anthemis microcephala (Schrenk) B. Fedtsch.), out of 6, except for the A. deserticola Krasch. & M. Pop. type. In the herbarial funds there have been studied in total 12 gherbarial samples of the only Red book type of Anthemis trotzkiana, meeting in the territory of Kazakhstan, including the own sample. The herbarial materials collected in the course of the field researches will fill up herbarial funds of Institute of botany and MES of RK phytointroduction, Al-Farabi Kazakh National University and K. Zhubanov Aktyubinsk regional state university. Results of research have theoretical value and can be used for the solution of questions of systematization. Key words: Asteraceae, Anthemis L., Anthemis trotzkiana Claus, rare species, herbarial funds.